Promoted Catalytic Properties of Acetone over Cerium-Modified Mullite Catalyst YMn2O5 - Xiaotian Mu; Wenhuan Wang; Kai Zhang; Honglei Ding; Weiguo Pan (Aerosol and Air Quality Research)
Abstract Mullite catalysts have become one of the most widely studied catalysts due to their highly stable structure and unique coordination with oxygen. In this work, Ce-modified mullite-type oxides Y1-xCexMn2O5 have been prepared by sol-gel method to explore their Cedoping amount-dependent catalytic performance for acetone elimination. Experimental results confirm that Y0.9Ce0.1Mn2O5 had optimum acetone oxidation activity, completely achieving 100% acetone conversion at 120°C under the reaction conditions of acetone concentration = 1000 ppm, 20 vol% O2/N2 and WHSV = 36000 mL g−1 h−1. This excellent catalytic activity comes from its larger specific surface area and higher Mn4+/Mn3+ molar ratio. XRD and TEM results show that YMn2O5 and CeO2 phases form a multiphase oxide and interfacial structure. XPS results show that the content of doped CeO2 mainly affects the surface adsorbed oxygen (Oads) and Mn4+ content of the catalyst. Manganese species with higher chemical states are indeed more favorable for oxidation reactions on manganese-based catalysts. In addition, the reduction temperature of mixed oxides shifts to the lower temperature region, indicating that manganese and cerium oxides are more reducible, where the mobility of oxygen species is greatly enhanced. Y0.9Ce0.1Mn2O5 also exhibits strong long-term stability and has good resistance to acetone elimination, showing excellent potential in eliminating acetone.